Budget impact and cost-effectiveness analyses of the COBRA-BPS multicomponent hypertension management programme in rural communities in Bangladesh, Pakistan, and Sri Lanka - Finkelstein, Eric A (ELSEVIER SCI LTD, 2023)
10.1016/S2214-109X(21)00033-4